(untitled) - L W Cottell (London, 1983)
The book covers the syllabuses of theoretical and practical Craft level examinations in refrigeration and air-conditioning. Key features of the book are: over 200 photographs and clearly labelled illustrations; glossary of important terms; sample examination papers for evaluation and revision; a "trouble-shooting" chart for identifying and remedying defects in equipment
Keywords: air conditioning - equipment and supplies,refrigeration and refrigerating machinery